Factors Associated With Risk of Neurologic Complications After Peripheral Nerve Blocks: A Systematic Review. (February 2017) - Sondekoppam, Rakesh V.; Tsui, Ban C. H.
Abstract : The onset of neurologic complications after regional anesthesia is a complex process and may result from an interaction of host, agent, and environmental risk factors. The purpose of this systematic review was examine the qualitative evidence relating to various risk factors implicated in neurologic dysfunction after peripheral nerve block (PNB). The MEDLINE, OVID, and EMBASE databases were primary sources for literature. Cochrane, LILACS, DARE, IndMed, ERIC, NHS, and HTA via Centre for Reviews and Dissemination (CRD; York University) databases were searched for additional unique results. Randomized controlled studies, case–control studies, cohort studies, retrospective reviews, and case reports/case series reporting neurologic outcomes after PNB were included. Relevant, good-quality systematic reviews were also eligible. Human and animal studies evaluating factors important for neurologic outcomes were assessed separately. Information on study design, outcomes, and quality was extracted and reviewed independently by the 2 review authors. An overall rating of the quality of evidence was assigned using GRADE (Grading of Recommendations Assessment, Development and Evaluation) criteria. Relevant full-text articles were separated based on type (prospective, retrospective, and nonhuman studies). Strengths of association were defined as high, moderate, inconclusive, or inadequate based on study quality and direction of association. The evidence from 77 human studies was reviewed to assess various host, agent, and environmental factors that have been implicated as possible risks. Most of the available evidence regarding the injurious effects of the 3 cardinal agents of mechanical insult, pressure, and neurotoxicity was extracted from animal studies (42 studies). Among the risk factors investigated in humans, block type had a strong association with neurologic outcome. Intraneural injection, which seems to occur commonly with PNBs, showed an inconsistent direction of association. Measures meant to increase precision and ostensibly reduce the occurrence of complications such as currently available guidance techniques showed little effect on the incidence of neurologic complications. Recovery from neurologic injury appears to be worse in patients with pre-existing risk factors. Categorization and definition of neurologic complication varied among studies, making synthesis of evidence difficult. Also, a significant portion of the evidence surrounding neurologic injury associated with PNB comes from animal or laboratory studies, the results of which are difficult to translate to clinical scenarios. Of the human studies, few had an a priori design to test associations between a specific risk factor exposure and resultant neurologic sequelae. A few risk factor associations were identified in human studies, but overall quality of evidence was low. Much of the evidence for risk factors comes from animal models and case reports. The final neurologic outcome seems to represent the complex interaction of the host, agent, and the environment. Abstract : Supplemental Digital Content is available in the text.